Seleção de professores temporários como estratégia na gestão da educação em municípios do Rio Grande do Sul - Linke, Denise Doná (2020)
This research aims to investigate how people management processes are configured in the recruitment and selection of teachers in Municipal Departments of Education (SMED) in the Brazilian State of Rio Grande do Sul. The analysis of how the SMEDs define and articulate the provision of the selection processes for teachers of the municipal public network in the State, as well as the identification of the definition of the desired profile of teachers for temporary admission to the municipal education network are the driving and guiding issues of this study. The research aims to contribute to the extent that it problematizes the practices of public selection processes of teachers, through discussions of principles of public management in the area of administration, in order to achieve more broadly and fully, the educational principles expressed in public policies. The theoretical corpus was consisted by the discussions of educational public policies, educational management, people management in the selection processes and challenges in the teaching exercise, especially the professional profile of the basic education teacher. The theoretical corpus consisted of discussions of educational public policies, educational management, people management in the selection processes and challenges in the teaching exercise, especially the professional profile of the basic education teacher. The qualitative research, through the method of non-probabilistic sampling, was conducted by semi-structured interviews with ten representatives of the SMEDs in the State of Rio Grande do Sul. The questions that guided the research were about the beginning of the selection processes and their mechanisms used, the perception of the efficiency of the results of the selection processes and the desired profile of the teacher. The data were analyzed using Bardin's content analysis technique (2016), which identifies the regularities and singularities considering the totality of the information collected. The results of the research indicate that the provision of resources is carried out in partnership with the various spheres of municipal government, following the formal precepts of public management processes. From the collected data, it is possible to infer two main questions: the first in relation to the need to conceive the whole selection process from the educational planning of the secretariats and educational establishments; the second, to rethink the recruitment and selection of teachers based on the specificity and nature of this function. The interviews indicate that the selection processes, while intentionality, express a dimension more practical than strategic and that although they tacitly consider a profile that refers to human dimensions, effectively the selections end up being restricted to formal and bureaucratic elements than precisely human and professional competence.